A new measure of tibiofemoral subchondral bone interactions that correlates with early cartilage damage in injured sheep. Issue 10 (11th July 2014) - Beveridge, Jillian E.; Heard, Bryan J.; Brown, Jevon J.Y.; Shrive, Nigel G.; Frank, Cyril B.
ABSTRACT We have demonstrated previously that chondral damage is associated with increased knee surface velocities following ligament and meniscus injuries in sheep. We tested the hypothesis that cartilage damage scores would correlate with a new bone surface interaction measure that captures complex changes in tibiofemoral alignment, "proximity disturbance" (PD). Six sheep underwent combined anterior cruciate and medial collateral ligament transection (ACL/MCLx), five complete lateral meniscectomy (Mx), and four sham arthrotomy (Sham). Tibiofemoral subchondral bone surfaces were modeled, and the post‐operative changes in relative separation of the surfaces (i.e., "proximity") were derived from subject‐specific in vivo 3D stifle kinematics. Surface areas of regions of near contact were determined, and PD was calculated as the range of change in tibiofemoral proximity, divided by normalized overlapping proximity surface areas between baseline and post‐operative time points. Cartilage morphology was graded at dissection. ACL/MCLx PD was significantly elevated relative to Mx and Shams, and correlated with cartilage damage (r2 = 0.88–0.98). Although not statistically significant, Mx PD values tended to be higher than those of Shams, and correlated with cartilage damage. Results from both injury models suggest that increasing change in tibiofemoral surface alignment may be increasingly deleterious to long‐term cartilage health in sheep. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1371–1380, 2014.